Seminar on Implementation of Pharmaceutical Service Standards During the Covid-19 Pandemic at Granmed Lubuk Pakam Hospital at 2020 - Sumitra, Jhoti; Br. Turnip, Nur Ulina M.; Sebayang, Loraetta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
Pharmacist pharmaceutical services for patients related to pharmaceutical preparations in order to improve the quality of pharmaceutical services in hospitals, the implementation of the Minister of Health Regulation no. 72 of 2016 concerning pharmaceutical service standards at Grandmed Hospitals with patient satisfaction during the Covid 19 2021 pandemic. Hospital pharmacy services involve pharmacists in order to supervise and control all activities related to healing treatment of sufferers in the aim of practicing patient safety standards which include Pharmaceutical supplies management activities starting from demand planning to controlling pharmaceutical supplies as well as clinical pharmacy service activities that are oriented towards reducing the risk of drug use errors in hospitals. This type of design was made by collecting data from 59 visiting patients at a certain point in time. Location at GrandMed Hospital Lubuk Pakam. The data obtained were compared with existing standards in the literature and analyzed using the chi-square test. It is known that out of 25 people (42.4%) respondents stated that clinical pharmacy services were not good. Of the 34 people (57.6%) respondents who stated that clinical pharmacy services were good for each employee, they had been given an understanding regarding clinical pharmacy services which had been socialized every morning briefing to maximize serving patients so that patients were satisfied with the services at Grandmed Hospital. This study can be concluded that the implementation of pmk no. 72 of 2016 there is a relationship between clinical pharmacy services and patient satisfaction during the Covid 19 pandemic at Grandmed Lubuk Pakam Hospital in 2021 (pvalue = 0.007).